2016
DOI: 10.1542/peds.2015-3859
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Assessment of Preterm Infants Treated With Darbepoetin and Erythropoietin

Abstract: BACKGROUND:We previously reported improved neurodevelopmental outcomes at 2 years among infants treated with the erythropoiesis-stimulating agents (ESAs) darbepoetin alfa (darbepoetin) or erythropoietin. Here we characterize 4-year outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 34 publications
(41 reference statements)
3
52
1
Order By: Relevance
“…Repeated low‐dose rhEpo treatment (500IU/kg, initiated within 72 hours, repeated every 48 hours for 2 weeks) significantly improved neurological outcomes in the Chinese RCT, indicating that continued treatment is essential, possibly because of successful stimulation of erythropoiesis and reduced red blood cell transfusions. This conclusion is in line with previous retrospective analyses of neurodevelopment in RCTs, which primarily aimed to reduce transfusions …”
supporting
confidence: 91%
“…Repeated low‐dose rhEpo treatment (500IU/kg, initiated within 72 hours, repeated every 48 hours for 2 weeks) significantly improved neurological outcomes in the Chinese RCT, indicating that continued treatment is essential, possibly because of successful stimulation of erythropoiesis and reduced red blood cell transfusions. This conclusion is in line with previous retrospective analyses of neurodevelopment in RCTs, which primarily aimed to reduce transfusions …”
supporting
confidence: 91%
“…58 Epo monotherapy, without hypothermia, may be useful for neonatal conditions other than HIE, such as perinatal stroke, 59 congenital heart disease, 60 and brain injury of prematurity. [61][62][63][64] This is the first clinical study of HIE that assesses biomarkers of efficacy to evaluate whether Epo provides additional neuroprotection to hypothermia. We found that Epo treatment was associated with significantly reduced severity of brain injury on MRI, specifically in the subcortical region (ie, the area that contains the basal ganglia, thalamus, and internal capsule).…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Because Epo levels may predict neurocognitive outcomes in human premature infants after erythropoietic Epo dosing (Bierer et al, ; Ohls et al, ), we studied several relationships that may predict brain weight. Through stepwise modeling, total brain Fe (µg) was the stronger predictor of brain weight, and although potentially the relationship between Epo and brain size might be a statistical anomaly, plasma Epo levels also predicted brain weight.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous Epo also exerts neuroprotective effects and is being studied in term newborns with hypoxic brain damage and premature infants (Bierer, Peceny, Hartenberger, & Ohls, ). Anemic premature infants with higher plasma Epo levels exhibit improved neurodevelopmental outcomes (Bierer et al, ; Ohls et al, ). Although not completely understood, preliminary work shows that Epo promotes oligodendrocyte differentiation to myelin‐producing cells and improves hippocampal dependent memory by modulating plasticity, synaptic connectivity and activity of memory‐related neuronal networks (Adamcio et al, ; Sugawa, Sakurai, Ishikawa‐Ieda, Suzuki, & Asou, ).…”
Section: Introductionmentioning
confidence: 99%